Characterization of deposited plasma spray NiCrAlCoY2O3 coating layers on AlMg1 alloy substrates - Darko Veljić; Časlav Lačnjevac; Marko Rakin; Darko Bajić (Zaštita Materijala)
In this paper, analyzed are the effects of the plasma spray distance on the microstructure and mechanical properties of the NiCrAlCoY2O3 coating layers deposited at atmospheric pressure. The microstructure and mechanical properties of the coating layers are under the influence of the interaction of plasma particles (ions and electrons) with powder particles, providing the transfer of velocity and temperature of the plasma particles onto the powder particles. The effect of the interaction is directly dependent on the time the powder particles were present in the plasma which is defined by distance of the plasma gun from the substrate, depending on the granulation of the powder, the melting point and specific gravity. In order to obtain homogeneous and denser coating layers with high adhesion, in the experiment three distances from the substrate were used: 95 mm, 105 mm and 115 mm. The layers were deposited on thin sheets of AlMg1 aluminum thickness of 0.6 mm. Evaluation of mechanical properties of the layers was carried out by examining microhardness using the HV0.1 method and the bond strength by tensile testing. The morphology of the powder particles was examined on the SEM, while the microstructure of the layers was evaluated under a light microscope in accordance with the Pratt Whitney standard. The results of the experiment showed that the distance from the substrate substantially influenced the structure and mechanical properties of the coating layers. The best deposited layers were examined in the system with the ZrO224%MgO ceramic coating, which have proved to be reliable protectionfrom high temperature and abrasive rocket jet fuel.